pH-Control in Aptamer-Based Diagnostics, Therapeutics, and Analytical Applications - Micaela Belleperche; Maria C. DeRosa (MDPI AG, 2018)
Aptamer binding has been used effectively for diagnostics, in-vivo targeting of therapeutics, and the construction and control of nanomachines. Nanostructures that respond to pH by releasing or changing affinity to a target have also been used for in vivo delivery, and in the construction of sensors and re-usable nanomachines. There are many applications that use aptamers together with pH-responsive materials, notably the targeted delivery of chemotherapeutics. However, the number of reported applications that directly use pH to control aptamer binding is small. In this review, we first discuss the use of aptamers with pH-responsive nanostructures for chemotherapeutic and other applications. We then discuss applications that use pH to denature or otherwise disrupt the binding of aptamers. Finally, we discuss motifs using non-canonical nucleic acid base pairing that can shift conformation in response to pH, followed by an overview of engineered pH-controlled aptamers designed using those motifs.